Features of Stimulating the Issue of Green Bonds in the Modern Economy - Borodin, Alex; Zaitsev, Vladislav; Shash, Nataliya; Chibisov, Kirill (International Journal of Energy Economics and Policy, 2023)
There are large number of companies that form investment portfolios of modern investors have a high level of CO2 emissions. In particular, such sectors of the economy include the oil and gas sector, metallurgy, electricity. For the transition of these sectors of the economy to a car-bon-neutral status, it is necessary to attract significant funding. One of the main instruments of such financing is green bonds. The purpose of the study is to develop a mechanism to encourage companies to implement green projects by issuing green bonds with coupon payments, which will be partially compensated. In the course of studying the problem posed, possible options for linking the Carbon Border Adjustment Mechanism (CBAM) and green bonds were also considered. The study was conducted on the basis of methods of comparison, modeling, analysis and deduction. The result of the work is the developed mechanism of tax incentives for the issuance of green bonds by companies, which can be applied in any country. The study was conducted taking into account the introduction of additional reducing coefficients to the mineral ex-traction tax, property tax and income tax. The study showed that in the case of partial compensation of coupon payments on bonds, the state does not need to introduce lowering coefficients to the tax rate, it is enough to use a tax deduction from income tax in the amount of the planned compensation of coupon payments.